A Biographic Researcher in Pursuit of an Aesthetic: The use of arts-based (re)presentations in “performative” dissemination of life stories - Jones, Kip (Qualitative Sociology Review, 2006)
The (re)presentation of biographic narrative research benefits greatly from embracing the art of its craft. This requires a renewed interest in an aesthetic of storytelling. Where do we find an aesthetic in which to base our new “performative” social science? The 20th Century was not kind to 18th Century notions of what truth and beauty mean. The terms need to be re-examined from a local, quotidian vantage point, with concepts such as “aesthetic judgment” located within community. Social Constructionism asks us to participate in alterior systems of belief and value. The principles of Nicolas Bourriaud’s Relational Aesthetics offer one possible set of convictions for further exploration. Relational Art is located in human interactions and their social contexts. Central to it are inter-subjectivity, being-together, the encounter and the collective elaboration of meaning, based in models of sociability, meetings, events, collaborations, games, festivals and places of conviviality. Bourriaud believes that Art is made of the same material as social exchanges. If social exchanges are the same as Art, how can we portray them? One place to start is in our (re)presentations of narrative stories, through publications, presentations and performances. Arts-based (re)presentation in knowledge diffusion in the post-modern era is explored as one theoretical grounding for thinking across epistemologies and supporting inter-disciplinary efforts. An example from my own published narrative biography work is described, adding credence to the concept of the research report/presentation as a “dynamic vehicle”, pointing to ways in which biographic sociology can benefit from work outside sociology and, in turn, identifying areas of possible collaboration with the narrator in producing “performances” within published texts themselves.